The transfer of technology to developing countries: Analytical concepts and economic policy aspects - Lutz Hoffmann (Intereconomics, 1985)
Although both the industrialised countries and the developing countries have an interest in the transfer of technology, there is a considerable amount of disagreement as to how the gains from the transfer should be apportioned. Professor Hoffmann offers a theoretical analysis of the mechanisms involved in technology transfer and in the determination of the transfer's price, and makes some suggestions as to the policies to be followed by the countries involved.
Keywords: 330; North-South Relations